Immunotherapy and MASLD-Related HCC: Should We Reconsider the Role of Etiology in the Therapeutic Approach to HCC? - Giuseppina Vizioli; Alberto Nicoletti; Daniela Feliciani; Barbara Funaro; Lorenzo Zileri Dal Verme; Francesca Romana Ponziani; Maria Assunta Zocco; Antonio Gasbarrini; Maurizio Gabrielli (Applied Sciences)
Hepatocellular carcinoma (HCC) accounts for 90% of primary liver cancers and typically arises in the context of chronic liver disease. With the increasing prevalence of metabolic disorders, metabolic dysfunction-associated steatotic liver disease (MASLD) has become the leading cause of chronic liver disease and the most rapidly increasing cause of HCC. The role of dysfunctional innate and adaptive immune responses in the development and progression of HCC is well-established, prompting numerous trials to evaluate the efficacy of immune checkpoint inhibitors (ICIs) in targeting tumor cells. These trials have yielded promising results, and ICIs, in combination with anti-vascular endothelial growth factor (VEGF) monoclonal antibodies, are now approved as first-line therapy for patients with metastatic or unresectable HCC, irrespective of the underlying liver disease. Notably, MASLD itself is characterized by immune system dysfunction, as metabolic inflammation plays a central role in its onset and progression. However, clinical studies and post-hoc analyses suggest that immunotherapy may be less effective in MASLD-associated HCC compared to viral-related HCC. This emerging evidence raises the question of whether the underlying liver disease influences the therapeutic response to ICIs in HCC. It may be time to consider tailoring therapeutic strategies for HCC based on the specific etiological, histological, and genotypical subgroups.